Joint space-time Huffman limited feedback precoding for spatially and temporally correlated MIMO channels - Mei-yan JU; Xin GE; Yue-heng LI; Guo-ping TAN (Tongxin xuebao)
For the MIMO channels with space correlation and time correlation, a novel joint space-time Huffman limited feedback precoding scheme was proposed which improves the system performance and reduces the amount of feedback. Based on space correlation, the precoding structure under zero-forcing (ZF) criterion was derived and the rotating quan-tization codebook was designed which reduces the effect of space correlation on system performance. In addition, in view of time correlation of channels, the scheme reduces the feedback data of channel state information (CSI) in the slow fad-ing channel by using neighborhood-based limited feedback. Due to different probabilities of codewords in the neighbor-hood, Huffman coding was adopted to further reduce the amount of feedback.